Sources and Characteristics of early journalism in Loja (Ecuador): 1856-1895 [Fuentes y características del primer periodismo lojano (Ecuador): 1856-1895] - Gonzalez Portela, M. (2017)
The birth and richness of early journalism of Loja, southern Ecuador, during the period from 1856 to 1895, is a phenomenon that has been insufficiently studied in the existing historiography. Although there have been efforts to study this period through the gathering and analysis of newspapers and magazines from the said province, research indicates that there are frequent inaccuracies and omissions in the data. What s more, studies carried out to date on this subject mostly lack descriptive analyses. This paper physically locates the 27 newspapers and 8 literary magazines that form almost the entire body of publications in this field. Through analysis and contextualization, it examines the usage of 91 leaflets, which serve not only as a fairly new phenomenon, but as a rich expression of public opinion.